Measurement of material volumes in a cylindrical silo using acoustic wave and resonance frequency analysis - Chukiet Sodsri (Institute of Advanced Engineering and Science, 2020)
This work presents an approach for measuring material volumes in a closed cylindrical silo by using acoustic waves and resonance frequency analysis of silo’s acoustic systems. With an assumption that the acoustical systems were linear and time-invariant, frequency responses of the systems were identified via measurement. A sine sweep was generated, amplified and fed to a loudspeaker inside the silo. Acoustic waves were picked up by a microphone and processed to yield the silo's frequency response. Resonance frequencies and wave mode numbers of standing waves in the frequency range below 900 Hz were analyzed and used for calculation of air-cavity lengths. With known silo's dimension, the material volume estimations were achieved. Sets of experiments for estimating volumes of sand, cement, water, rice grain, and stone flakes in a closed silo, were done. It was found that the approach could successfully estimate the volumes of sand, cement, and water with a satisfactory accuracy. Percent errors of the estimations were less than 3% from the actual volumes. However, the approach could not estimate the volume of rice grain and stone flakes, since their sound refractions were neither resulted in standing waves nor acoustical modes in the silo.